Unicode flaw leaves most software open to malicious code injection. Issue 11 (November 2021) - Unknown
Abstract : Researchers at Cambridge University have discovered a trick that could allow someone to insert malicious functionality into source code in a way that's unlikely to be picked up by either automated or manual code reviews. This could open the way to serious software supply chain attacks, especially with open source repositories.